2012
DOI: 10.1063/1.4749246
|View full text |Cite
|
Sign up to set email alerts
|

Water dissociation on Cu (111): Effects of molecular orientation, rotation, and vibration on reactivity

Abstract: Three-dimensional time-dependent quantum mechanical method has been used to study the influence of orientation, rotation, and vibration on the dissociation of water molecule on Cu(111) surface, using London-Eyring-Polanyi-Sato potential energy surface. Our calculations show that dependency of dissociation probability on the initial orientation of the molecule changes with the vibrational state of the molecule. It has also been found that for v(0) = 0 and 1, where v(0) stands for the vibrational state of the ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 40 publications
6
27
1
Order By: Relevance
“…Earlier quantum dynamical studies on water dissociation on Cu(111) surface showed enhancement in reactivity with vibrational excitation. [18][19][20][21] Detailed quantum studies on mode selectivity in H 2 O dissociation on Cu(111) surface reported similar softening of symmetric stretching and bending modes, leading to enhancement in reactivity. 21 They attributed this increase to the "late" barrier for this reaction.…”
Section: E Transition State Geometries and Vibrational Frequenciesmentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier quantum dynamical studies on water dissociation on Cu(111) surface showed enhancement in reactivity with vibrational excitation. [18][19][20][21] Detailed quantum studies on mode selectivity in H 2 O dissociation on Cu(111) surface reported similar softening of symmetric stretching and bending modes, leading to enhancement in reactivity. 21 They attributed this increase to the "late" barrier for this reaction.…”
Section: E Transition State Geometries and Vibrational Frequenciesmentioning
confidence: 96%
“…19 In both cases, increase in reactivity is attributed to "late" barrier for reaction. Effect of molecular orientation, rotation, and vibration on water dissociation on Cu(111) surface on a low dimensional LEPS PES 20 and on a quasi-7-D PES 21 are also available in literature. These investigations illustrate the significance of excitation in orientational, rotational, and vibrational states on the dissociation probability in detail.…”
Section: Introductionmentioning
confidence: 99%
“…We note in passing that similar mode specificity was observed by others using a much cruder model. 149 The strong mode specificity in these theoretical studies strongly suggests that the DC process is dominated by dynamics and different forms of energy have different efficacies in promoting the reaction. Subsequently, this 6D model was used to study bond selectivity in the DC of HOD.…”
Section: A H 2 Omentioning
confidence: 98%
“…43,44 Similar conclusions have been reached by others with a lower dimensional model. 45 This should not come as a surprise as H 2 O, like CH 4 , has slow IVR, 24 and its interaction with transition metal surfaces is also characterized by PESs with a "late" barrier. [46][47][48][49][50][51][52] Our theoretical model predicted that all three vibrational modes enhance the reactivity more efficiently than translational energy, underscoring their strong coupling with the reaction coordinate.…”
Section: Introductionmentioning
confidence: 99%